PERANCANGAN LEARNING MANAGEMENT SYSTEM SEBAGAI PENDUKUNG PEMBELAJARAN JARAK JAUH - Phie Chyan (Rabit : Jurnal Teknologi dan Sistem Informasi Univrab, 2021)
The distance education system (PJJ), which is perceived as a 21st century innovation, is an education system that has broad outreach across space, time and socioeconomics. The PJJ system opens access to education for anyone, anywhere and at any time. In 2018, the gross enrollment rate of higher education in Indonesia will reach 33.3%. still far from achieving the national target, which is 50% by 2024. This research focuses on designing a Learning Management System (LMS) to support the application of distance learning. The LMS that is developed will be able to support the preparation, presupposition and distribution of teaching materials, the process of learning assessment in various forms of learning evaluation models and to support interactions between instructors and students through various forms of interaction using audio visual media. The results obtained are an LMS that is able to meet the needs of teaching and learning in distance and blended learning.